Diet of the maned wolf (Chrysocyon brachyurus) and its role in seed dispersal on a cattle ranch in Brazil - Santos, E. F.; Setz, EZF; Gobbi, N. (Cambridge University Press, 2003)
The maned wolf Chrysocyon brachyurus is the largest canid inhabiting South America. Its geographic distribution includes the open fields of Brazil's central area, which is currently undergoing agricultural expansion. The diet of the maned wolf and its seasonal variation was determined on a dairy cattle ranch (Sao Luis farm, 566 ha) in the State of Minas Gerais, Brazil. From January to December faeces of the maned wolf were collected monthly (n = 150 scats; 397 food item occurrences). Twenty-nine taxa were identified from scats, 18 of animal origin (46% or 183 occurrences) and 11 of plants (54% or 214 occurrences). The fruits of Solanum lycocarpum were the dominant food item in our study (29%). Mammals contributed 13%, arthropods 12%, birds 11% and reptiles 2% of the food items. Arthropods and fruits were prevalent in the rainy season and mammals in the dry season. As expected for a heavily fanned region, frugivory results were at the lower end of the diversity scale (9-33 species) and included four old garden species. No previous study of the diet of maned wolf has registered as many species of Solanaceae as this one. Although dietary richness was lower, the main food items (wolf fruit, armadillos, rodents, birds) were the same as study sites in 'cerrado' and upland meadows. In this region, the open habitats occupied by the maned wolf were previously covered by Atlantic forest, suggesting that landscape modification such as cattle ranching has opened new frontiers for distribution expansion of the maned wolf. The impact of loss of dietary richness and the increase in Solanaceae on the survival of the maned wolf need to be evaluated.
Keywords: Chrysocyon brachyurus; dairy cattle ranch; diet; maned wolf; Minas Gerais State; scat; Brazil